A 20-year real-world study on drug survival and predictive factors for infliximab discontinuation in Behçet’s syndrome - Talarico, Rosaria; Sulis, Antonello; Di Cianni, Federica; Marinello, Diana; Manca, Maria Laura; Mosca, Marta (Frontiers in Immunology, 2025)
ObjectiveInfliximab (IFX) is an immunosuppressive drug widely used for the treatment of patients with Behçet’s syndrome (BS) with severe or refractory organ involvements. The aim of this study was to evaluate IFX survival, clinical response and safety profile in a monocentric cohort of BS patients.MethodsPatients with BS treated with IFX intravenously across a 20-year period were retrospectively-prospectively examined. Total duration of therapy and drug retention until the end of follow-up were calculated, as well as the reasons of discontinuation, including adverse events. Clinical response, expressed as changes in BDCAF (Behçet’s Disease Current Activity Form) indexacross the follow-up period, were evaluated and compared among patients.ResultsSixty patients with BS were treated with IFX over a 20-year period. Overall drug retention was 45%, with survival rates of 78.3% at 1 year, 63.3% at 2 years, and 35% at 5 years (median duration 37 months, IQR 17–72). Most discontinuations occurred after 24 months and were mainly due to loss of efficacy (25%), de novo manifestations (21%), or allergic reactions (18%). Clinical activity improved markedly, with a mean BDCAF reduction of 4 points, ranging from −3.0 in mild to −5.7 in highly active disease. Continuers showed lower BDCAF scores at last follow-up and achieved higher remission and major response rates compared with discontinuers. Younger age and female sex were associated with higher discontinuation risk. Over the two decades, IFX indications shifted from major-organ involvement to predominantly refractory muco-cutaneous disease.ConclusionsIFX showed good safety profile and excellent clinical response in this real-world BS cohort, with a drug survival of 45% within a median treatment duration of 37 months.